Comparing young children's oral and written story retelling: the role of ideation and transcription. - McIntyre, Anne; Scott, Amy; McNeill, Brigid; Gillon, Gail (Speech, Language & Hearing, 2025)
This study compared 76 six-year-old children's performance on matched oral and written narrative retell tasks. Other predictors of children's written story retell ability were also examined (i.e., oral narrative comprehension, phoneme awareness, spelling, and reading). Analyses of four groups, based on the number of words produced in the oral and written retells, were undertaken to identify the underlying factors contributing to children's written retell performance. Children's oral and written retells were strongly correlated on almost every measure, and children produced a significantly greater number of words in their oral retells. Hierarchical linear modelling found that 79% of the variance in written retell scores was explained by ideation (47%) and transcription measures (32%). The findings of this study demonstrate how ideation and transcription skills interact during the writing process and highlight the need for educators to address the key foundational skills that support children's early writing success, during the first years of instruction.